Facing moral dilemmas as a method: Teaching ethical research principles to geography students in higher education - Wintzer, Jeannine; Baumann, Christoph (Research Ethics in Human Geography, 2022)
Field diary entries of Fabienne Kaufmann, Master's student at the Geographical Institute of the University of Berne. The field diary entries cited here illustrate four geographical practices: First, surveying the earth, second, determining and attributing properties to territories, third, assigning persons and communities to local, regional or national spaces and fourth, in addition to the material products of surveying, attributing and locating, and as a consequence of geographical practices, (re)producing the power of passing on information from ‘others’. In collecting data in Kenya and evaluating it in Switzerland, the Master student whose fieldnotes are cited above experiences moral dilemmas that result from the conflicting demands of fulfilling the research tasks set by the research group, while at the same time adhering to morally correct actions. The student also recognises that the persons responsible for the project did not reflect on the research project, for example by questioning the goals pursued by the sponsors.<br
CRIS-Team WoS Importer:2022-10-28